The dangerous book for boys - Iggulden, Conn.; Iggulden, Hal. (New York : Harper Collins Publishers, 2007)
For every boy from eight to eighty, covers essential boyhood skills such as building tree houses, learning how to fish, finding true north, and even answering the age-old question of what the big deal with girls is. In this digital age there is still a place for knots, skimming stones and stories of incredible courage. This book recaptures Sunday afternoons, stimulates curiosity, and makes for great father-son activities. The brothers Conn and Hal have put together a collection of all things that make being young, or young at heart, fun--building go-carts and electromagnets, identifying insects and spiders, and flying the world's best paper airplanes.--From publisher description.
Hagerstown Library Memorial Book for Carl Wright given by George & Susan Catania & Family.
1 3 6 8 9 13 17 18 19 21 23 25 31
Keywords: Handbooks, vade-mecums, etc; Amusements; Recreation; Boys -- Miscellanea